Penggunaan Media Instagram Dalam Menulis Karangan Narasi - Avit Kurniasari (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
The purpose of this study was to determine the ability to write narrative essays using Instagram social media in the form of photos with the theme of holidays in seventh grade students of the As-Saudiyah Islamic Education Foundation. The method used in this research is using a qualitative method. The subjects of this study were 27 narrative texts written by students of class VII B in the odd semester of the As-Saudiyah Islamic Education Foundation which were carried out offline. The results showed that the ability to write narrative texts in class VII B of the As-Saudiyah Islamic Education Foundation was included in the fairly good category with an average grade of 75,55. It can be seen that 12 of 27 students with a percentage of 44,4% scored in the very good category, 13 out of 27 students with a percentage of 48,1% scored in a good category, 2 of 27 students with a percentage of 7,4 % obtained a score in the poor category. Keywords: Writing, Narrative Text, Instagram Social Media